Aplicação da Estratigrafia de Seqüências para Caracterização em Multiescala de Reservatórios no Grupo Guatá (Eopermiano da Bacia do Paraná) na Região de São Gabriel - RS, Brasil - KÜCHLE, JULIANO; HOLZ, MICHAEL (Pesquisas em Geociências, 2002)
<!– .p text-align: justify; –> Detailed stratigraphic analysis of the Early Permian Rio Bonito and Palermo Formations of the intracratonic Paraná Basin in the region of São Gabriel County has been used for a study on reservoir characterization of paralic sandstones. Two main depositional systems were recognized, a fluvial-dominated delta system at the base and a wavedominated barrier island system at the top, with an intervening succession characterized by a delta system with alternated wave and fluvial influence. The succession is divided in two third-order depositional sequences, enclosing thirteen fourthorder parasequences. This high-resolution stratigraphic framework was the base for a multiscale approach on reservoir characterization of the paralic sandstone bodies of the two sequences. Reservoir heterogeneities are discussed, starting from the scale of depositonal sequence (heterogeneity level 1), passing down to heterogeneity at the scale of systems tracts (heterogeneity level 2) and finalizing with an approach at parasequence scale (heterogeneity level 3). Main control on heterogeneity at the first level - depositional sequences - is base-level variation as generating mechanism for unconformities (sequence boundaries) and the sediment type and rate. At the second level -systems tracts - the reservoir heterogeneity is controlled by the lateral and vertical variations in thickness of particular systems within the different systems tracts and by the stratigraphic signatures of the bounding surfaces (sequence boundaries, transgressive surfaces and flooding surfaces), and at the third level the minor flooding surfaces control internal heterogeneity, reservoir continuity and connectivities between reservoirs. At this scale, five paralic reservoir bodies were recognized, with thickness range from 5 to 25 meters. The study has a twofold importance: it is useful as a predictive tool for similar geologic settings in producing oil fields, and may also be used for geologic characterization of the aquifer in the study area.